PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN 161 PEKANBARU - Mahera, Anis; Hermita, Neni; M, Lazim (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2019)
The background of this study was the low grade V social studies learning outcomes of SDN 161 Pekanbaru with an average of 65.83. Therefore this study aims to improve social studies learning outcomes in class V. Research is Classroom Action Research (CAR) which consists of four stages, namely planning, implementation, observation and reflection. The subjects in this study were class V.C as many as 30 students consisting of 12 men and 18 women. The results showed that classical completeness in the first cycle was 63.33% which increased in the second cycle by 86.66%. Teacher activities increased at each meeting, namely 70.83%, 79.16%, 83.33%, and 87.5%. Likewise, student activity experienced an increase in each of which was 58.33%, 66.66%, 79.16%, and 87.5%. The average basic score to the first cycle increased by 12.65% and the base score to the second cycle increases by 33.16%. Based on the research that has been carried out, it can be concluded that the application of the cooperative learning model of the type of student facilitator and explaining can improve the learning outcomes of Social Sciences class V at SDN 161 Pekanbaru